Nutraceutical potential and antioxidant benefits of selected fruit seeds subjected to an in vitro digestion. (January 2016) - Chen, Guan-Lin; Chen, Song-Gen; Chen, Fu; Xie, Ying-Qing; Han, Men-Di; Luo, Chun-Xia; Zhao, Ying-Ying; Gao, Yong-Qing
Highlights: New information on the antioxidants of fruit seeds. Multiple methods for the measurement of total antioxidant capacity were highlights. This study supplied much new information for researches of food and pharmaceuticals. The relations between antioxidant capacities and total phenolic content were studied Abstract: In order to find new sources of natural antioxidants, total phenolic contents and antioxidant capacities of 11 fruit seeds before and after in vitro digestion were evaluated by Folin–Ciocalteu method, 2, 2-diphenyl-1-picrylhydrazyl radical scavenging activity assay (DPPH), ferric reducing antioxidant power assay (FRAP), and ABTS + scavenging activity (ABTS) assay, respectively. The correlations between DPPH, FRAP, ABTS values and total phenolic contents were also evaluated. The results showed that 11 fruit seeds had diverse antioxidant capacities and the variation was very large. Furthermore, the main compounds of 11 fruit seeds were identified and quantified. Four fruit seeds, Dimocarpus longgana Lour, Vitis vinifera Linn (red), Vitis vinifera Linn (black), and Litchi chinensis Sonn showed the strongest antioxidant activities whether before or after digestion, which implied that these fruit seeds are important natural sources for preventing oxidative stress diseases.